Correlation of telomere length in brain tissue with peripheral tissues in living human subjects - Carver, Annemarie J.; Hing, Benjamin; Elser, Benjamin A.; Lussier, Stephanie J.; Yamanashi, Takehiko; Howard, Matthew A.; Kawasaki, Hiroto; Shinozaki, Gen; Stevens, Hanna E. (Frontiers in Molecular Neuroscience, 2024)
Telomeres are important to chromosomal stability, and changes in their length correlate with disease, potentially relevant to brain disorders. Assessing telomere length in human brain is invasive, but whether peripheral tissue telomere length correlates with that in brain is not known. Saliva, buccal, blood, and brain samples were collected at time points before, during, and after subjects undergoing neurosurgery (n = 35) for intractable epilepsy. DNA was isolated from samples and average telomere length assessed by qPCR. Correlations of telomere length between tissue samples were calculated across subjects. When data were stratified by sex, saliva telomere length correlated with brain telomere length in males only. Buccal telomere length correlated with brain telomere length when males and females were combined. These findings indicate that in living subjects, telomere length in peripheral tissues variably correlates with that in brain and may be dependent on sex. Peripheral tissue telomere length may provide insight into brain telomere length, relevant to assessment of brain disorder pathophysiology.